PROGRAM BIMBINGAN UNTUK PENGEMBANGAN PERILAKU PROSOSIAL ANAK USIA DINI MELALUI METODE DONGENG - Melina , Tenny Septiani Rachman d Lestari (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract: Among the various aspects that need is developed at an early age is a period in which there is a social aspect of prosocial behavior. Early childhood in the present face enormous challenges as they seek to develop prosocial behavior because of the program that is likely to cause aggressive behavior of children. To develop it requires media and appropriate methods, ideal and effective, and appropriate method is through a fairy tale. The aim of this study were: 1) to describe the objective conditions prosocial behavior early childhood; 2) describe the objective conditions of the program to develop prosocial behavior; and 3) develop a mentoring program to develop students' prosocial behavior through methods of fairy tales. This study used a qualitative approach with descriptive methods. The subjects were 15 students of class B RA. Suhayah Kampung Melayu, East Jakarta. The data collection instrument used was the observation and interview guides are made by the research team. Based on the analysis of the data obtained the following results: 1) In general, students of class B have not been fully prosocial behavior; 2) There are no special programs to develop students' prosocial behavior; 3) Program guidance to develop prosocial behaviors early childhood through fairy tales methods that have been made through the stacking author be some stages: preparation program development.Keywords: voluntary counseling, prosocial behavior, a fairy tale.